Failure analysis of the Ge-substituted Li6PS5I with bare LiNi0.8Co0.1Mn0.1O2 and performance improvement via Li2ZrO3 coating. Issue 41 (6th October 2022) - Zhang, Ziqi; Yao, Jingming; Yu, Chuang; Xu, Ruonan; Ma, Jun; Wei, Chaochao; Peng, Linfeng; Zhang, Long; Cheng, Shijie; Xie, Jia
Abstract : A facile synthesis of a Ge-substituted Li6 PS5 I electrolyte with a high ionic conductivity of 13.1 mS cm −1 is reported, along with the failure analysis and performance improvement of solid-state batteries using LiNi0.8 Co0.1 Mn0.1 O2 cathodes. Abstract : Inorganic sulfide solid electrolytes with high ionic conductivity and low interfacial resistance attract extensive research attention. Here, we successfully synthesize Li6.7 P0.3 Ge0.7 S5 I argyrodite electrolyte with ultrahigh Li-ion conductivity (13.1 mS cm −1 at room temperature) and low activation energy (0.19 eV). All-solid-state lithium batteries based on the prepared electrolyte and pristine LiNi0.8 Co0.1 Mn0.1 O2 cathode show fast capacity degradation due to the side reaction between the active materials and Li6.7 P0.3 Ge0.7 S5 I electrolytes. XRD and TEM results confirm the existence of MnO2 and Ni3 S2 at the interface between the pristine cathode and solid electrolyte, leading to high resistance and poor electrochemical performances. SEM results indicate that the large volume changes during cycling also contribute to the deteriorating battery performance. A thin layer of the Li2 ZrO3 coating layer is then applied onto the surface of cathode materials, which delivers superior capacity properties and cyclability at ambient temperature. The coated electrode also delivers a high area capacity of 5.1 mA h cm −2 with an ultrahigh area loading of 26.8 mg cm −2 at 0.5C at ambient temperature when combined with the Li6.7 P0.3 Ge0.7 S5 I electrolytes. Moreover, the assembled battery offers an initial discharge capacity of 107.8 mA h g −1 at 0.1C at −20 °C and maintains a capacity retention of 62% after 200 cycles.